Ground Penetration Radar Using Golay Sequences - Vazquez Alejos, A.; Muhammad, D.; Ur Rahman Mohammed, H. (2007 IEEE Region 5 Technical Conference, 2007)
In most of the existing ground penetration radar (GPR) systems, the major problem is low signal-to-noise ratio (SNR) and the masking of the weaker returns by the strong side-lobes. These twin problems can be minimized to a large extent with the help of Golay sequences. Golay sequences are complementary sequences; the sum of these yield twice the value of the autocorrelation at zero lag and zero elsewhere. In terms of improved SNR and reduced sidelobe levels, the performance of these sequences is considered to be better than that of pseudorandom binary sequences (PRBS), Barker or other maximal length sequences. Some of the results from a bench-top Golay based GPR system using PRBS and Golay codes are presented.